The Early Activation of CD8+ T Cells Is Dependent on Type I IFN Signaling following Intramuscular Vaccination of Adenovirus Vector. (27th May 2014) - Hemmi, Masahisa; Tachibana, Masashi; Tsuzuki, Sayaka; Shoji, Masaki; Sakurai, Fuminori; Kawabata, Kenji; Kobiyama, Kouji; Ishii, Ken J.; Akira, Shizuo; Mizuguchi, Hiroyuki
Abstract : Few of the vaccines in current use can induce antigen- (Ag-) specific immunity in both mucosal and systemic compartments. Hence, the development of vaccines that realize both mucosal and systemic protection against various pathogens is a high priority in global health. Recently, it has been reported that intramuscular (i.m.) vaccination of an adenovirus vector (Adv) can induce Ag-specific cytotoxic T lymphocytes (CTLs) in both systemic and gut mucosal compartments. We previously revealed that type I IFN signaling is required for the induction of gut mucosal CTLs, not systemic CTLs. However, the molecular mechanism via type I IFN signaling is largely unknown. Here, we report that type I IFN signaling following i.m. Adv vaccination is required for the expression of type I IFN in the inguinal lymph nodes (iLNs), which are the draining lymph nodes of the administration site. We also showed that the type I IFN signaling is indispensable for the early activation of CTLs in iLNs. These data suggested that type I IFN signaling has an important role in the translation of systemic innate immune response into mucosal adaptive immunity by amplifying the innate immune signaling and activating CTLs in the iLN.